2005
DOI: 10.1093/jn/135.7.1673
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Increases Human Oxaluria and Kidney Stone Risk

Abstract: Currently, the recommended upper limit for ascorbic acid (AA) intake is 2000 mg/d. However, because AA is endogenously converted to oxalate and appears to increase the absorption of dietary oxalate, supplementation may increase the risk of kidney stones. The effect of AA supplementation on urinary oxalate was studied in a randomized, crossover, controlled design in which subjects consumed a controlled diet in a university metabolic unit. Stoneformers (n = 29; SF) and age- and gender-matched non-stoneformers (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(90 citation statements)
references
References 23 publications
1
86
1
2
Order By: Relevance
“…Despite its numerous positive roles in the metabolism, vitamin C serves as an oxalate precursor because it is partially metabolized into oxalate. Increased urinary oxalate excretion was observed in humans that consumed 1000 mg ascorbic acid per day (84). Similarly, the same study that reported a benefi cial role for vitamin B6 in a large number of human participants failed to fi nd any signifi cant effect of vitamin C at doses from 250 mg per day to 1500 mg per day (80).…”
Section: Compounds and Other Factors That Modulate Urine Oxalate Concmentioning
confidence: 84%
See 1 more Smart Citation
“…Despite its numerous positive roles in the metabolism, vitamin C serves as an oxalate precursor because it is partially metabolized into oxalate. Increased urinary oxalate excretion was observed in humans that consumed 1000 mg ascorbic acid per day (84). Similarly, the same study that reported a benefi cial role for vitamin B6 in a large number of human participants failed to fi nd any signifi cant effect of vitamin C at doses from 250 mg per day to 1500 mg per day (80).…”
Section: Compounds and Other Factors That Modulate Urine Oxalate Concmentioning
confidence: 84%
“…Similarly, the same study that reported a benefi cial role for vitamin B6 in a large number of human participants failed to fi nd any signifi cant effect of vitamin C at doses from 250 mg per day to 1500 mg per day (80). Recent studies have suggested that a more individual approach should be taken in testing the consumption of vitamin C during oxalate urolithiasis, since the participants, being stone-formers or not, either did not respond to the treatment (60 %) or responded with an increased excretion of urinary oxalate (84). In contrast to the effect of vitamin C, which is metabolised to oxalate, when used in an experimental model on living epithelium, vitamin C can abolish crystal formation in a free radical-rich environment, most likely due to its antioxidant properties (54).…”
Section: Compounds and Other Factors That Modulate Urine Oxalate Concmentioning
confidence: 99%
“…19 Hence, any condition that increases oxalate absorption from food may lead to increased oxalate production and cause calcium oxalate stone formation. 20 Massey et al (2005) reported that 1000 mg ascorbic acid twice each day increased urinary oxalate and Tiselius Risk Index (TRI) for calcium oxalate kidney stones in 40% of participants, both stone formers and non-stone formers. 21 The patients in present study were great consumers of leafy Naseem Aslam Channa, Allah Bux Ghangro, Ali Muhammad Soomro, et al 16 Reduced urinary pH could be an important risk factor for uric acid stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…20 Massey et al (2005) reported that 1000 mg ascorbic acid twice each day increased urinary oxalate and Tiselius Risk Index (TRI) for calcium oxalate kidney stones in 40% of participants, both stone formers and non-stone formers. 21 The patients in present study were great consumers of leafy Naseem Aslam Channa, Allah Bux Ghangro, Ali Muhammad Soomro, et al 16 Reduced urinary pH could be an important risk factor for uric acid stone formation. 22,23 For acidification of urine, several processes are responsible.…”
Section: Discussionmentioning
confidence: 99%
“…Oxalates are also excreted in urine if VC ingestion is excessive. Hence, in a genetically predisposed individual a high VC intake can increase the risk of calcium oxalate kidney stones [25,34].…”
Section: Adverse Effects Of Vitamin Cmentioning
confidence: 99%